Newman, Vatican II, and the Triple Office. (12th June 2012) - Phillips, Peter
Abstract Although not directly quoted in the documents of Vatican II, Newman should be regarded as an 'invisible Father' of the Council. This is evident the Council Fathers' recognition of the importance of the historical situation as the place for practicing theology, a recognition of 'the signs of the times'. We encounter revelation as fact rather than a set of hand‐me‐down propositions. Both Newman and Vatican II appreciated the role that the whole community of the Church plays in the articulation of doctrine. Newman invoked the model of the priestly, prophetic and regal office conferred on the Church by her Lord to challenge the increasing polarization between teachers and taught in the church and the damaging centralism that ensued. In a similar way the Council wished to restore a fruitful interplay between periphery and centre by acknowledging the collegiality of the bishops, and calling for a full involvement of laity in the life of the Church.